Comparison of gut microbiome and plasma metabolome profiles between domesticated and wild Eurasian perch (Perca fluviatilis). (24th May 2022) - Chen, Xiaowen; Hou, Xin; Qian, Long; Ai, Tao; Xu, Qinyu; Xiang, Wei; Hu, Bolin; Wang, Jun; Wang, Chenghui
Abstract: Domestication has strongly influenced the physiological characteristics of fish due to selection pressure from human beings and local environments. Here, we comprehensively analysed the gut microbiome and plasma metabolome through 16S rRNA sequencing and untargeted metabolomic detection using liquid chromatography–mass spectrometry. We found significant divergences in the gut microbiota and plasma metabolome between domesticated and wild Perca fluviatilis . The reduced abundance of Proteobacteria in the gut and lowered abundance of L‐lysine, L‐valine, piperidine, beta‐alanine, L‐glutamate and L‐histidine in the plasma metabolome of domesticated P. fluviatilis indicated potential reduced protein digestion and absorption capability in domesticated P. fluviatilis . By constrast, the increased abundance of Bacteroidetes in the gut might imply the improved digestive capability for plant polysaccharides in domesticated P. fluviatilis . Digestive system alterations may be due to changed selection pressures on diet during long‐term domestication. Our study provided preliminary results on the physiological changes in domesticated and wild P. fluviatilis which will affect the digestive system and growth performance of P. fluviatilis . The data obtained in this study will benefit germplasm improvement programmes for P. fluviatilis in the future.